2001
DOI: 10.1159/000049489
|View full text |Cite
|
Sign up to set email alerts
|

DNA Arrays in Allergy and Immunology

Abstract: The DNA array technique allows the simultaneous analysis of multiple genes. This makes it an interesting tool for studies of gene expression in various diseases that are caused by or depend on multiple genes. DNA arrays are particularly applied to define certain immunological conditions such as allergic diseases. We summarize strategies on gene expression profiling of inflammatory disease and immunologically relevant cells using DNA array technology. Using DNA arrays, gene expression analysis of CD4+ T cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Collectively, these studies indicate that individual immune responses typically involve up-regulation of multiple hundreds of genes (7)(8)(9). This technology has also been applied in the allergy field to study Th2 responses and related signaling pathways in freshly isolated T cells (10), polyclonally stimulated T cells (11,12), allergen-specific T cell clones and lines (13,14), polarized Th1/Th2 cell lines (15)(16)(17)(18)(19)(20), and in animal models (21). A consistent finding in the studies was the substantial number of differentially expressed genes identified, however, the lack of consistency in the gene lists reported by each study is striking.…”
mentioning
confidence: 99%
“…Collectively, these studies indicate that individual immune responses typically involve up-regulation of multiple hundreds of genes (7)(8)(9). This technology has also been applied in the allergy field to study Th2 responses and related signaling pathways in freshly isolated T cells (10), polyclonally stimulated T cells (11,12), allergen-specific T cell clones and lines (13,14), polarized Th1/Th2 cell lines (15)(16)(17)(18)(19)(20), and in animal models (21). A consistent finding in the studies was the substantial number of differentially expressed genes identified, however, the lack of consistency in the gene lists reported by each study is striking.…”
mentioning
confidence: 99%
“…CCL22 has been shown to play an important role in various diseases and mouse disease models. For example, elevated levels of CCL22 have been found in affected tissue of patients suffering from atopic dermatitis (10), atopic asthma (10), and contact hypersensitivity (11). Furthermore, CCL22 has been shown to be critically involved in mouse models of allergen-induced lung inflammation (12), atopic dermatitis (13), and septic peritonitis (14).…”
mentioning
confidence: 99%
“…In addition, no appropriate cell lines are available for further in vitro functional studies, other than leukemic cell lines such as Eol1 (Saito et al 1985) and AML14.3D10 (Baumann and Paul 1998). Recent developments in the technology of gene expression analysis, such as differential display (DD) (Liang and Pardee 1992;Ito et al 1994), DNA microarray (Schmidt-Weber et al 2001;Granucci et al 2001), and real-time RT-PCR (Lie and Petropoulos 1998;Kafert et al 1999) make it possible to efficiently survey the expression of large numbers of genes in small amounts of clinical samples, and new data on eosinophil accumulation and actions in pathological conditions are being accumulated.…”
Section: Comprehensive Gene Expression Analysis In Eosinophils From Pmentioning
confidence: 99%